2007
DOI: 10.1029/2007gl029576
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant properties of atmospheric and model humic‐like substances (HULIS)

Abstract: Surface‐active organics such as humic‐like substances (HULIS) are abundant in aerosol particles and can lower the surface tension of cloud droplets forming on secondary organic and biomass burning aerosols. How fast is the diffusion of these species, relative to the time scale of cloud droplet growth? Here we report surface tension measurements of solutions containing HULIS extracted from smoke and pollution aerosol particles as well those of molecular weight‐fractionated aquatic fulvic acids. Diffusion coeffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
83
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(90 citation statements)
references
References 34 publications
7
83
0
Order By: Relevance
“…Note that ρ ion is given using the fitted surface tensions while in Table 3 the corresponding numbers for the κ R model are listed using the surface tension of pure water. (Ziese et al, 2008) 9.51E−06 E2 5434 HULIS, second sample, Budapest, Hungary (Ziese et al, 2008) 2.14E−05 E2 5268 HULIS, LBO night, Rehovot, Israel (Ziese et al, 2008) 3.51E−05 E2 3516 HULIS, LBO day, Rehovot, Israel (Ziese et al, 2008) 3.57E−05 E2 7317 HULIS, 3WSFA, Rehovot, Israel (Ziese et al, 2008) 2.68E−05 E2 13 269 surface tension and, thereby, reduce the critical supersaturation Taraniuk et al, 2007;Wex et al, 2007). For a surface tension of water, both models overestimate the critical supersaturation by a factor of ∼2.…”
Section: Comparison Ccn Measurements and Model Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that ρ ion is given using the fitted surface tensions while in Table 3 the corresponding numbers for the κ R model are listed using the surface tension of pure water. (Ziese et al, 2008) 9.51E−06 E2 5434 HULIS, second sample, Budapest, Hungary (Ziese et al, 2008) 2.14E−05 E2 5268 HULIS, LBO night, Rehovot, Israel (Ziese et al, 2008) 3.51E−05 E2 3516 HULIS, LBO day, Rehovot, Israel (Ziese et al, 2008) 3.57E−05 E2 7317 HULIS, 3WSFA, Rehovot, Israel (Ziese et al, 2008) 2.68E−05 E2 13 269 surface tension and, thereby, reduce the critical supersaturation Taraniuk et al, 2007;Wex et al, 2007). For a surface tension of water, both models overestimate the critical supersaturation by a factor of ∼2.…”
Section: Comparison Ccn Measurements and Model Resultsmentioning
confidence: 99%
“…Of this organic fraction, about 10-60% has been found to be water soluble organic carbon (WSOC) (Krivacsy et al, 2001;Kleefeld et al, 2002). Until now, the knowledge about the hygroscopic growth and CCN properties of the multitude of water soluble organic compounds found in aerosol particles has been very limited (Kanakidou et al, 2005;Dinar et al, 2006Dinar et al, , 2007Taraniuk et al, 2007;Wex et al, 2007).…”
mentioning
confidence: 99%
“…It has been observed that a 10% change in the effective SS can cause a ∼40% change in calculations of the critical diameter. The effect of surfactants such as humic-like substances further depends on their dissolution and diffusion rates [Taraniuk et al, 2007]. Several other factors contribute to potential uncertainties in , some of which have been listed in previous studies [Chang et al, 2010].…”
Section: Aerosol Hygroscopicity and Degree Of Oxygenationmentioning
confidence: 99%
“…As yet, these isolation and characterization approaches have not been applied to dust, although hulis and BC in aerosol have been widely studied in the past (Havers et al, 1998;Krivácsy et al, 2000;Dinar et al, 2006;Taraniuk et al, 2007;Kirchstetter et al, 2008;Dutkiewicz et al, 2009;Sýkorová et al, 2009). In the present study, we isolated HAs, kerogen and black carbon (KB) and BC from dust collected in Guangzhou, China, and then characterized the chemical composition of the fractionated macromolecule organic matter using elementary analysis (EA), X-ray diffraction (XRD), organic petrographic examination (OPE), scanning electron microscopy (SEM), solid state 13 C cross-polarization and magic angle spinning nuclear magnetic resonance spectroscopy ( 13 C-CP/MAS NMR) and Fourier transformed infrared spectroscopy (FTIR).…”
Section: Introductionmentioning
confidence: 99%